Diferentes modelos, diferentes caminhos: a busca pela sustentabilidade ambiental no município de Piratini, RS - Sell, Jaciele Carine (2012)
The development has become a goal to be achieved at any cost; regardless of the consequences and/or negative impacts that may cause for certain social groups, the point is to elevate any community to the level of consumption and of material wealth of the great world powers. Recognizing the unsustainability of this model of progress and their worrying and unbridled expansion at the gaucho s territory, arises the need to analyze it through a systemic approach, considering since its environmental scope until the social and economic. Comprising the sustainability from the encounter of knowledge, cultures, creatures and ways of meaning of the nature diversified we choose the landscape as category of analysis, precisely because of its systemic character. The landscape brings in its own essence the understanding of the transformation and of the dynamics. Regardless of the scale, the landscape is composed of elements which interact through the exchange of matter and energy. These exchanges, however, does not occur naturally only. Political, economical and, sometimes, social interests interfere in the dynamics of the landscapes, making them more susceptible to degradation or not. This degradation can be defined as an increase of entropy, this is, loss or dispersion of the energy existing in the elements that make up the system. It is from this perspective that it is aimed in this work compare the flow of energy between two agro-ecosystems inserted into the Pampa biome and differentiated by projects of society in dispute, seeking to highlight the system that loses more energy in its production process. One of the agro-ecosystem refers to a large property with a monoculture practice of plantation of exotic trees, specifically acacia; the other agro-ecosystem it is characterized as a cooperative formed by farmers settled from the Landless Peasants Movement, that collectively make use of the principles of the agro-ecology, both for production and for their way of life. Through field works was possible the elaboration of two comparative diagrams that show the amount of input, the (re)use and (re)investment of energy and what is actually exported/generated from the system. In this representation is clear that the agro-ecosystem which most suffers the loss of energy, which needs more foreign investment and which provides the largest portion of the imbalance and of the environmental degradation, despite its ambitious economic output, is the tillage of trees. Besides showing high entropy of the point of view of energy and natural resources, this monoculture model is responsible for a large social "clutter" in the local.